Effect of maleic acid on onset temperature and H2 release kinetics for thermal dehydrogenation of ammonia borane. (27th November 2020) - Kim, Geo Jong; Hunt, Savannah G.; Hwang, Hyun Tae
Abstract: Ammonia borane (AB, NH3 BH3 ) has received great attention as an attractive hydrogen storage candidate because it has high hydrogen contents and releases hydrogen under mild operating conditions. Despite the favorable properties, AB thermolysis has several drawbacks such as long induction period, slow kinetics, and relatively high onset temperature, compared to hydrolysis approach. In this study, hydrogen release properties from AB were investigated in the addition of maleic acid (C4 H4 O4, MA). Using thermogravimetric analysis, temperature programmed reaction with mass spectrometry, and FTIR analyses, the solid and gaseous products generated by thermolysis of the AB-MA mixture were characterized to understand the reaction mechanism. It was found that with the addition of MA, hydrogen yield and release kinetics were enhanced, while the onset temperature reduced significantly to ~60 °C. It is likely that the hydrolysis between O–H bonds in MA and B–H bonds in AB was initiated, and the heat released from the hydrolysis triggers the thermolysis of AB. It was also confirmed that a combination of the two additives (MA and boric acid) enables a further increase of H2 yield while the onset temperature remains at ~60 °C. Our results suggest that MA is a promising additive to improve AB dehydrogenation. Highlights: Using maleic acid, a high H2 equivalent from AB was obtained with fast kinetics. The onset temperature of dehydrogenation was significantly reduced to ~60 °C. Hydrolysis between OH– and BH– bonds initiated ammonia borane dehydrogenation. 2.11H2 equivalents were achieved at 60 °C by a combination of multiple additives.